Arf and Rho GAP adapter protein ARAP1 participates in the mobilization of TRAIL-R1/DR4 to the plasma membrane - Šímová, Šárka; Klíma, Martin; Čermák, Lukáš; Horová, Vladimíra; Anděra, Ladislav (Apoptosis, 2008)
TRAIL, a ligand of the TNFalpha family, induces upon binding to its pro-death receptors TRAIL-R1/DR4 and TRAIL-R2/DR5 the apoptosis of cancer cells. Activated receptors incite the formation of the Death-Inducing Signaling Complex followed by the activation of the downstream apoptotic signaling. TRAIL-induced apoptosis is regulated at multiple levels, one of them being the presence and relative number of TRAIL pro- and anti-apoptotic receptors on the cytoplasmic membrane. In a yeast two-hybrid search for proteins that interact with the intracellular part (ICP) of DR4, we picked ARAP1, an adapter protein with ArfGAP and RhoGAP activities. In yeast, DR4(ICP) interacts with the alternatively spliced ARAP1 lacking 11 amino acids from the PH5 domain. Transfected ARAP1 co-precipitates with DR4 and co-localizes with it in the endoplasmic reticulum/Golgi, at the cytoplasmic membrane and in early endosomes of TRAIL-treated cells. ARAP1 knockdown significantly compromises the localization of DR4 at the cell surface of several tumor cell lines and slows down their TRAIL-induced death. ARAP1 overexpressed in HEL cells does not affect their TRAIL-induced apoptosis or the membrane localization of DR4, but it enhances the cell-surface presentation of phosphatidyl serine. Our data indicate that ARAP1 is likely involved in the regulation of the cell-specific trafficking of DR4 and might thus affect the efficacy of TRAIL-induced apoptosis.
Keywords: apoptóza; Carrier Proteins; transport proteinů; buněčné linie; lidé; RNA, Small Interfering; Cell Membrane; Financing, Organized; transportní proteiny; financování organizované; mapování interakce mezi proteiny; Apoptosis; Cell Line, Tumor; Cell Line; techniky dvojhybridového systému; Down-Regulation; TNF-Related Apoptosis-Inducing Ligand; Humans; down regulace; Protein Transport; protein TRAIL; GTPase-Activating Proteins; Two-Hybrid System Techniques; buněčná membrána; malá interferující RNA; Receptors, Tumor Necrosis Factor; Protein Interaction Mapping; nádorové buněčné linie; receptory TNF; proteiny aktivující GTPasu